One-Pot Synthesis of Quinoxalines Starting from Aldehydes Under Metal-Free Conditions - Hu, Zhong-Yuan; Du, Ding; Tang, Wei-Fang; Lu, Tao (Asian Journal of Chemistry, 2012)
An efficient and convenient synthesis of quinoxalines from easily available aldehydes was performed as a one-pot procedure in good to excellent yields under metal-free conditions, via sequential benzoin condensation, aerobic formation of benzils and condensation of the latter with 1,2-diaminobenzenes.